1995
DOI: 10.1200/jco.1995.13.11.2776
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, surgical adjuvant clinical trial of recombinant interferon alfa-2a in selected patients with malignant melanoma.

Abstract: Our findings indicate trends that suggest a possible benefit for selected patients with high-risk malignant melanoma. The results will require further study in a larger patient population for confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(64 citation statements)
references
References 19 publications
0
61
0
3
Order By: Relevance
“…In stage III disease, one of three high-dose therapeutic trials showed a significant improvement of progression-free survival, and another trial demonstrated improved survival in the initial evaluation [397,399,400]. Concerning low-dose therapy in stage III disease, only one of 6 trials revealed improvement in progression-free and overall survival [375,396,399,[401][402][403].…”
Section: Adjuvant Interferon Therapymentioning
confidence: 99%
“…In stage III disease, one of three high-dose therapeutic trials showed a significant improvement of progression-free survival, and another trial demonstrated improved survival in the initial evaluation [397,399,400]. Concerning low-dose therapy in stage III disease, only one of 6 trials revealed improvement in progression-free and overall survival [375,396,399,[401][402][403].…”
Section: Adjuvant Interferon Therapymentioning
confidence: 99%
“…three times a week for 12 weeks. At median follow-up of 6.1 years, neither disease-free nor overall survival were significantly greater with treatment (Creagan et al, 1995).…”
Section: Does Adjuvant Interferon Offer Survival Benefit?mentioning
confidence: 79%
“…Both the ECOG and Intergroup studies indicate this, and there was a similar trend in a smaller North Central Cancer Treatment Group high dose study (Creagan et al, 1995). However, around four-fifths of patients treated with high-dose interferon experience moderate or severe toxicity.…”
mentioning
confidence: 75%